Recent Trends in Physics of Material Science and Technology - Gaol, Ford Lumban; Shrivastava, Keshav; Akhtar, Jamil (Springer Series in Materials Science, 2015)
This book discusses in detail the recent trends in Computational Physics, Nano-physics and Devices Technology. Numerous modern devices with very high accuracy, are explored In conditions such as longevity and extended possibilities to work in wide temperature and pressure ranges, aggressive media, etc. This edited volume presents 32 selected papers  of the 2013 International Conference on Science & Engineering in Mathematics, Chemistry and Physics . The book is divided into three  scientific Sections: (i) Computational Physics, (ii) Nanophysics and Technology, (iii) Devices and Systems and is addressed to Professors, post-graduate students, scientists and engineers taking part in R&D of nano-materials, ferro-piezoelectrics, computational Physics and devices system, and also different devices based on broad applications in different areas of modern science and technology.